Hasya Yoga Jalan Menuju Pencerahan - Semadi, Gusti Ngurah Yoga (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Hasya yoga is a one of the concept of yoga which not yet familiar in the Hinduism general peoples. Teaching Hasya yoga is a considering from yoga teaching which one can get live to be health, harmony, peace full and prosperous. Every human being want to get all those in the world.Yoga rightnow already to be model or trend, on the some way is to become way of life.In fact live is not perfect, many people want to get life prosperous, long live, harmonies, and etc., but is not to be essay to get them.In this live we need one think to make balancing between physical and spiritual. One of them is practicing yoga. When we are doing yoga, step by step make the mind will be strong. Human being need control their mind, because very difficult how to control it. Hence, to get balancing in our mind is the first and very important in the yoga teaching. The mind can calm down when following yoga. Hasya yoga which the last in teaching yoga that considering along with blooming period which completely past full of dynamic, where human being need doing many refreshing with make laugh and live full of joyful.